Convergent synthesis of a tetrasaccharide repeating unit of the O-specific polysaccharide from the cell wall lipopolysaccharide of Azospirillum brasilense strain Sp7 - Mandal, Pintu Kumar; Dhara, Debashis; Misra, Anup Kumar (Beilstein Journal of Organic Chemistry, 2014)
A straightforward convergent synthesis has been carried out for the tetrasaccharide repeating unit of the O-specific cell wall lipopolysaccharide of the strain Sp7 of Azospirillum brasilense. The target tetrasaccharide has been synthesized from suitably protected monosaccharide intermediates in 42% overall yield in seven steps by using a [2 + 2] block glycosylation approach.
Keywords: Azospirillum brasilense; glycosylation; lipopolysaccharide; plant growth-promoting bacteria (PGPB); tetrasaccharide